Music, language and autism : exceptional strategies for exceptional minds - Ockelford, Adam, 1959- (Philadelphia : Jessica Kingsley Publishers, 2013)
'Children with autism often have an intense natural musicality. This book explains how music and language'work' as systems of communication, and why music holds such a fascination for many young people on the autism spectrum. There are strategies for showing how music can be used to support language development and even substitute for verbal communication. Exploring the progression from a young child's intuitive engagement with music, to using it as a scaffold for communication, socialisation and understanding, the book illustrates, through the use of detailed case studies, how music nurtures a sense of self and provides a positive outlet to express inner thoughts and feelings without resorting to challenging or even destructive behaviours.
Presenting an innovative approach to the use of music with people on the autism spectrum, this book will be a fascinating resource for speech and language therapists, music therapists, occupational therapists, teachers, teaching assistants, educational psychologists, carers and parents of people with autism.'--pub. desc.
Reflections on autism -- The challenge of language -- Making sense of music -- How musicality develops -- Music, language and communication -- Exceptional early cognitive environments (EECEs) -- Teaching the'1 in 20.'
Includes bibliographical references and index.
Keywords: Music therapy for children; Autistic children -- Language; Autistic children -- Education; Autism in children